2019
DOI: 10.1101/2019.12.19.19015321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of Quasi-Continuous Blood Pressure based on Harmonic Phase-Shifts in Signals using Non-Invasive Photoplethysmographic Measurements

Abstract: According to the guidelines of the European Society of Hypertension International Protocol revision 2010, the requirements for long time blood pressure measurement (BPM) are: simple handling, robustness against movements, accuracy of better than 5 mmHg, and, above all, that the patient's motion should not be restricted during measurement. These requirements are in particular important for a reliable interpretation of the blood pressure (BP) of hypertensive patients, because such a diagnosis will usually be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…In addition, Sherebrin et al demonstrated that the power of harmonics decreased with age or arteriosclerosis 45 . Kern et al used PPG harmonics for human blood pressure estimation 46 . In their opinion, the phase velocities of the fundamental and higher harmonics of PPG depend on the (nonlinear) elastic properties of the artery.…”
Section: Physiological Basis Of the Proposed Featuresmentioning
confidence: 99%
“…In addition, Sherebrin et al demonstrated that the power of harmonics decreased with age or arteriosclerosis 45 . Kern et al used PPG harmonics for human blood pressure estimation 46 . In their opinion, the phase velocities of the fundamental and higher harmonics of PPG depend on the (nonlinear) elastic properties of the artery.…”
Section: Physiological Basis Of the Proposed Featuresmentioning
confidence: 99%